2007
DOI: 10.1086/510621
|View full text |Cite
|
Sign up to set email alerts
|

Velocity Structure in the Orion Nebula. I. Spectral Mapping in Low-Ionization Lines

Abstract: High-dispersion echelle spectroscopy in optical forbidden lines of O 0 , S + , and S 2+ is used to construct velocity-resolved images and electron density maps of the inner region of the Orion nebula with a resolution of 10 km s −1 × 3 ′′ × 2 ′′ . Among the objects and regions revealed in this study are (1) the Diffuse Blue Layer: an extended layer of moderately blue-shifted, low-density, low-ionization emission in the southeast region of the nebula; (2) the Red Bay: a region to the east of the Trapezium where… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 50 publications
4
41
0
Order By: Relevance
“…28. The two higher velocity (17 v Hα 21 km s −1 ) regions were discussed by García-Díaz & Henney (2007); they were named Red Bay for the region east of the Trapezium, and Red Fan for the part just north of the western end of the Bright Bar. The elongated structure of lower velocities between Red Bay, Bright Bar, and Red Fan was discussed in Doi et al (2004) and named Big Arc with a less pronounced eastern component (11 v Hα 14 km s −1 in our data) and a stronger and longer southern part (3 v Hα 14 km s −1 in the MUSE data).…”
Section: Electron Temperature/densitymentioning
confidence: 99%
“…28. The two higher velocity (17 v Hα 21 km s −1 ) regions were discussed by García-Díaz & Henney (2007); they were named Red Bay for the region east of the Trapezium, and Red Fan for the part just north of the western end of the Bright Bar. The elongated structure of lower velocities between Red Bay, Bright Bar, and Red Fan was discussed in Doi et al (2004) and named Big Arc with a less pronounced eastern component (11 v Hα 14 km s −1 in our data) and a stronger and longer southern part (3 v Hα 14 km s −1 in the MUSE data).…”
Section: Electron Temperature/densitymentioning
confidence: 99%
“…Listings of the arguably best earlier studies of the ionized side (facing θ 1 Ori C) and neutral side (mostly molecules) are presented in (Walmsley 2000;O'Dell et al 2008). More recently there have been additional valuable observational studies (van der Wiel et al 2009;Mesa-Delgado et al 2011) and models (Henney 2005b;Pellegrini et al 2009;Shaw et al 2009;Ascasibar et al 2011). García-Díaz & Henney (2007 present evidence for several other bar structures, but none are as obvious as the Bright Bar.…”
Section: The Bright Barmentioning
confidence: 99%
“…Obviously, in order to obtain a structure function over a wide range of scales, very high quality data with an ample spatial coverage are required. In the case of longslit spectra, this is a non-trivial task, not least the cali-brating of the positions of the slits (García-Díaz & Henney 2007;García-Díaz et al 2008). Chandrasekhar (1949) suggested that turbulence is ubiquitous in astrophysics and that it could be analysed statistically via the spectrum of the velocity field, which expresses the correlations between instantaneous velocity components at all possible pairs of points in the medium.…”
Section: Introductionmentioning
confidence: 99%